Price Dynamics in Limit Order Markets - Parlour, Christine A. (Review of Financial Studies, 1998)
This article presents a one-tick dynamic model of a limit order market. Agents choose to submit a limit order or a market order depending on the state of the limit order book. Each trader knows that her order will affect the order placement strategies of those who follow and the execution probability of her limit order is endogenous. All traders take this into account which, in equilibrium, generates systematic patterns in transaction prices and order placement strategies even with no asymmetric information. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.